(untitled) (Bangladesh Journal of Pharmacology, 2014)
Vicia sativa is traditionally used medicinal plant in skin infections, asthma, bronchitis, urinary diseases and also used as antiseptic, anti-poison, aphrodisiac, anti rheumatic and antipyretic. In the present study n-hexane extract of V. sativa was evaluated for the antibacterial activity against pathogenic bacteria Staphylococcus aureus, Bacillus atrophaeus, Escherichia coli and S. epidermidis by disc diffusion method. Minimum inhibitory concentration of the n-hexane extract against all bacteria was determined by broth dilution method. Preliminary phytochemical analysis and HPLC analysis showed the presence of a number of bioactive constituents which exhibits antibacterial activity. So the current study showed that V. sativa possesses the significant antibacterial activity.